Food and beverage cost control - Dopson, Lea R.; Hayes, David K. (US.: John Wiley & Sons, 2020)
"This chapter presents the relationship among a foodservice business's revenue, expenses, and profit. As a professional foodservice manager, you must understand the relationship that exists between controlling these three areas and the resulting success of your operation. In addition, the chapter presents the mathematical foundation you must know to report your operating results and express them as a percentage of your revenue or budget. This method is a standard within the hospitality industry"--
Includes bibliographical references and index.
Keywords: Food service -- Cost control